2020
DOI: 10.3390/metabo11010008
|View full text |Cite
|
Sign up to set email alerts
|

Using Out-of-Batch Reference Populations to Improve Untargeted Metabolomics for Screening Inborn Errors of Metabolism

Abstract: Untargeted metabolomics is an emerging technology in the laboratory diagnosis of inborn errors of metabolism (IEM). Analysis of a large number of reference samples is crucial for correcting variations in metabolite concentrations that result from factors, such as diet, age, and gender in order to judge whether metabolite levels are abnormal. However, a large number of reference samples requires the use of out-of-batch samples, which is hampered by the semi-quantitative nature of untargeted metabolomics data, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The study was conducted in accordance with the Declaration of Helsinki. Z-scores were calculated using two different approaches: 1) metabolites which were annotated in at least 7 batches were merged, a Box-Cox transform was applied, normalized using Metchalizer (Bongaerts, et al, 2020) and the Z-scores were determined using a regression model with age and sex as covariates (Bongaerts, et al, 2020), 2) for metabolites which were annotated in less than 7 batches, the Z-scores were determined from 15 within-batch samples, where abundancies were first Box-Cox transformed and normalized using Probabilistic Quotient Normalization (PQN). When a metabolite was annotated in both positive- and negative ion mode, the Z-score of the ion mode with the largest median abundancy (over all samples) was taken.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in accordance with the Declaration of Helsinki. Z-scores were calculated using two different approaches: 1) metabolites which were annotated in at least 7 batches were merged, a Box-Cox transform was applied, normalized using Metchalizer (Bongaerts, et al, 2020) and the Z-scores were determined using a regression model with age and sex as covariates (Bongaerts, et al, 2020), 2) for metabolites which were annotated in less than 7 batches, the Z-scores were determined from 15 within-batch samples, where abundancies were first Box-Cox transformed and normalized using Probabilistic Quotient Normalization (PQN). When a metabolite was annotated in both positive- and negative ion mode, the Z-score of the ion mode with the largest median abundancy (over all samples) was taken.…”
Section: Methodsmentioning
confidence: 99%
“…Z-scores were calculated using two different approaches. Metabolites that were annotated in at least 7 batches were merged, a Box-Cox transform was applied and normalized using Metchalizer [16]. Z-scores were determined using a regression model with age and sex as covariates [16].…”
Section: Z-score Calculationmentioning
confidence: 99%
“…Metabolites that were annotated in at least 7 batches were merged, a Box-Cox transform was applied and normalized using Metchalizer [16]. Z-scores were determined using a regression model with age and sex as covariates [16]. For metabolites that were annotated in less than 7 batches, the Z-scores were determined from 15 within-batch samples, where abundancies were first normalized using Probabilistic Quotient Normalization [17] and Box-Cox transformed.…”
Section: Z-score Calculationmentioning
confidence: 99%
“…NGMS allows the simultaneous measurement of hundreds of metabolites, circumventing the need for targeted metabolic tests based on patient phenotype as a first‐tier screening for IMDs. Several studies have demonstrated the effectiveness of NGMS for screening IMDs in individual patients with a well‐described set of diagnostic biomarkers 2–7 . However, many patients still lack a definitive diagnosis when restricting the analysis to known biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of NGMS for screening IMDs in individual patients with a well-described set of diagnostic biomarkers. [2][3][4][5][6][7] However, many patients still lack a definitive diagnosis when restricting the analysis to known biomarkers. Looking for ways to systematically analyse a larger set of metabolites present within the NGMS data is the next logical step.…”
mentioning
confidence: 99%